Determinação espectrofotométrica de citrato de sildenafil em formulações farmacêuticas - Weinert, Patrícia Los [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Sociedade Brasileira de Química, 2008)
This paper describes a simple and rapid spectrophotometric method for quantitative determination of sildenafil citrate based on its reaction with p-chloranil accelerated by hydrogen peroxide, producing a stable purple compound (λmax= 535 nm). In the absence of peroxide this reaction is very slow. The experimental conditions were optimized by using response surface methodologies. Beer's law is obeyed in a concentration range of 8.52 x 10-5 - 1.70 x 10-3 mol L-1 (r = 0.999). The detection limit was 1.96 x 10-5 mol L-1. The method was successfully applied for the determination of sildenafil citrate in medicines with good accuracy and precision.
Spectrophotometric determination of sildenafil citrate in pharmaceutical formulations
Keywords: sildenafil citrate; p-chloranil; spectrophotometry